Literature Review Relationship Between Stress Levels and Lecturer’s Performance In 2022 - Tampubolon, Lindawati F.; Sigalingging, Vina Yolanda Sari; Sahetapy, Meirlin (Sean Institute, 2022)
Lecturer performance is work achievement achieved by lecturers with academic responsibilities. Low lecturer performance can lead to poor work results and unable to complete the work. One of the factors that can affect the performance of lecturers is work stress. A high workload can cause work stress due to working under time pressure to achieve the target so that work productivity decreases. When the stress level experienced is higher, the lecturer's performance decreases. This systematic review aims to explore information and analyze the relationship between stress levels and lecturer performance. Descriptive research with a systematic review method is the research design used. The research collects several journals related to the topic through research from the online google undergraduate database for review and analysis. The results of the journal search obtained 40 journals in accordance with the inclusion criteria. Based on the analysis of the relationship between stress levels and lecturer performance from 10 journals, it was found that 10 journals (100%) said that stress levels were closely related to lecturer performance. The level of stress is very important for lecturers in carrying out the duties of the Tri Dharma of Higher Education. Suggestion: It is hoped that the control with job design and gathering activities every 6 months can reduce stress levels at work.